KEKUATAN HUKUM BATIKMARK SEBAGAI SARANA PERLINDUNGAN PRODUK BATIK DI INDONESIA - Devi Andani (Jurnal Justiciabelen, 2018)
This study aims to find out how legal force and consequence of batikmark as protection of batik products in Indonesia. The problem raised is: How legal force of batikmark as protection of batik products in Indonesia?; and Howconsequence of batikmark as protection of batik products in Indonesia? This study includes qualitative research with normative legal research typology. Research data was collected throught literature study, documents, and interviews. Then all data collectedwritten descriptively and analyzed qualitatively.The results of this study show that batikmark as protection of batik products in Indonesia have legal force like constitution. But, batikmark implemented for batik entrepreneurs in Indonesia not effective yet. Proven by the small number of batikmark certificates given by Balai Kerajinan dan Batik until September 2012. Furthermore, whwn viewed from batik entrepreneurs, batikmark implemented not effective yet because no sanctions have been imposed if batik entrepreneurs have not implemented batikmark. Consequence of batikmark there are legal of implemented batikmark is batik products are given quality assurance, throuhgt batikmark can increase consumer trust because batik quality has certain criteria; and batikmark as a differentiator between Indonesian batik or foreign batik. This study recommends the improvement and renewal rule of law of batikmark; socializayion and introduction to batikmark forbatik entrepreneurs in Indonesia.